Intervención fisioterapéutica en paciente de sexo masculino de 35 años de edad en fascitis plantar - Toaza Casalombo, Jazer Eliseo (2024)
Patient, a 35-year-old male and a merchant by profession, presented with acute symptoms related to plantar fasciitis in the right foot, evidenced by an initial score of 8 on the Visual Analog Scale (VAS) to assess pain intensity. A treatment approach focused on relieving pain and improving functionality was implemented. This approach included physiotherapy sessions that specifically addressed the plantar fascia and the Achilles tendon through stretching techniques, along with exercises aimed at strengthening the muscles of the lower extremities. Additionally, the use of kinesiotape was integrated as an integral part of the treatment to provide additional support. As the treatment progressed, a marked decrease in pain intensity was observed, reaching a final score of 3 on the VAS scale at the end of the treatment period. These results highlight the effectiveness of physiotherapy and the interventions applied in addressing plantar fasciitis, allowing the patient to improve his quality of life and reintegrate into his daily activities.